Analysis Content Of Copper (Cu) And Manganese (Mn) In Carrot (Daucus Carota L.) With Atomic Absorption Spectrophotometry Methods - Afniati Lanas; Amrin Amrin; Bahrizal Rizal (Jurnal Periodic Jurusan Kimia UNP, 2013)
Carrots (Daucus Carrota L.) is widely grown vegetables. Soil as the growth of vegetables such as carrots can be contaminated media by harmful substances, such as heavy metals. Has done research on the analysis of copper and manganese in the carrots in the area Talago Koto Baru, Tanah Datar and area Bangkaweh,Agam with Atomic Absorption Spectrophotometry method. This study aims to determine the content of copper (Cu) and manganese (Mn) in the carrots and to determine the type of good solvent in the analysis of copper (Cu) and manganese (Mn) in carrot by Atomic Absorption Spectrophotometry method. This study uses a wet destruction method, where the destruction is done with some variation of the solvent variation: pa HClO4, HNO3 pa, pa and HNO3-HClO4 (4:1). Research results showed that carrot in the area Talago Koto Baru, Tanah Datar and area Bangkaweh,Agam is still below safe limits but should still be on the alert. Best solvent for metal content analysis of Cu and Mn in the sample carrots for area Talago Koto Baru, Tanah Datar and area Bangkaweh, Agam is HNO3 pa.